(untitled) (International Journal of Engineering and Computer Science, 2015)
The growth rate of the internet exceeds day by day. With the fast growth of internet, there is need to protect the sensitive data from unauthorized access. Cryptography plays a major role in the field of network security. There are many encryption techniques available currently to secure the data. Cryptography can be defined as the art or science of altering information or change it to a chaotic state, so that the real information is hard to extract during transfer over any unsecured channel. Latest advancements in technology and new concepts like quantum cryptography have added a complete new dimension to data security. The strength of this cryptographic technique comes from the fact that no one can read (or steal) the information without altering its content. This alteration alerts the communicators about the possibility of a hacker and thus promising a highly secure data transfer. Audio cryptography can be employed in audio distribution for the purpose of guaranteeing the confidentiality. Electronic commerce in audio products would be facilitated by the development of solutions which can ensure security/privacy, efficiency in compressed domain to reduce the bandwidth requirements, flexibility of implementing progressive audio quality control and computationally inexpensive to be used in real-time systems. Audio cryptography aims to minimize the residual intelligibility of the original audio and control the access to only authorized users. It is similar to but not a direct application of normal cryptographic techniques. The main advantage is that scrambled audio are still validly formatted which can be played by the corresponding players. In this research work, a novel method for audio encryption is proposed using random permutation with multiple key applications. The proposed method would not only provide highly secure audio but also efficient for audio file having higher frequency band. MATLAB R2013a has been used as an implementation platform using signal processing tool box.